An Analysis of Students' Speaking Problems in Learning English - Lihami, Sri; Sada, Clarry; Wardah, Wardah (Universitas Cokroaminoto Palopo, 2024)
This research aims to describe the English-speaking problems the students face and investigate the factors that cause speaking problems in linguistics and non-linguistics. The data were collected through close-ended questionnaires and semi-structured interviews. The participants in this study were 68 accounting students in SMKN 7 Pontianak in the academic year 2023/2024. The research findings showed that 68% of students were categorized as students with a high level of speaking problems, 8% were classified as students with a very high level of speaking problems, and 24% were categorized as students with a low level of speaking problems. The research findings also reveal that students have a higher level of speaking issues in linguistics and non-linguistics. The research topic being discussed for the student problems in speaking performance was financial statements. Several speaking problems were found in linguistics and non-linguistics. Students’ speaking problems were found in linguistics, such as vocabulary, pronunciation, grammar, fluency, and comprehension. In addition, students’ speaking problems were found in non-linguistics, such as anxiety, shyness, being afraid to make mistakes, low participation, and lack of motivation.